Effect of Curvature Shape of Transparent COVID-19 Protective Face Shields on the Speech Signal - BJELIĆ, Miloš; MIJIĆ, Miomir; MILJKOVIĆ, Tatjana; ŠUMARAC PAVLOVIĆ, Dragana (Archives of Acoustics, 2024)
Recent papers and studies over the course of last three years have shown that COVID-19 has a negative impact on the speech communication quality between people. This paper presents an influence analysis of the curvature shape of protective transparent shields on the speech signal. Five shields made of the same material and dimensions but with different curvatures were analyzed, from a completely flat to a very curved shield which has the same shape of curvature at its top and bottom and covers the entire face. The influence of the shield is analyzed with two types of experiments – one using dummy head with integrated artificial voice device, and the other using real speakers (female and male actors). It has been shown that usage of protective shields results in a relative increase in the speech signal level, in the frequency range of around 1000 Hz, compared to the situation when protective shields are not used. The relative increase in speech signal levels for large-curvature shields can be up to 8 dB. The possible causes of this phenomenon have been analyzed and examined.